Reversal strategies for vitamin K antagonists in acute intracerebral hemorrhage. Issue 1 (14th May 2015) - Parry‐Jones, Adrian R.; Di Napoli, Mario; Goldstein, Joshua N.; Schreuder, Floris H. B. M.; Tetri, Sami; Tatlisumak, Turgut; Yan, Bernard; van Nieuwenhuizen, Koen M.; Dequatre‐Ponchelle, Nelly; Lee‐Archer, Matthew; Horstmann, Solveig; Wilson, Duncan; et al.
<x xml:space="preserve">Abstract</x> Objective There is little evidence to guide treatment strategies for intracerebral hemorrhage on vitamin K antagonists (VKA‐ICH). Treatments utilized in clinical practice include fresh frozen plasma (FFP) and prothrombin complex concentrate (PCC). Our aim was to compare case fatality with different reversal strategies. Methods We pooled individual ICH patient data from 16 stroke registries in 9 countries (n = 10 282), of whom 1, 797 (17%) were on VKA. After excluding 250 patients with international normalized ratio < 1.3 and/or missing data required for analysis, we compared all‐cause 30‐day case fatality using Cox regression. Results We included 1, 547 patients treated with FFP (n = 377, 24%), PCC (n = 585, 38%), both (n = 131, 9%), or neither (n = 454, 29%). The crude case fatality and adjusted hazard ratio (HR) were highest with no reversal (61.7%, HR = 2.540, 95% confidence interval [CI] = 1.784–3.616, p < 0.001), followed by FFP alone (45.6%, HR = 1.344, 95% CI = 0.934–1.934, p = 0.112), then PCC alone (37.3%, HR = 1.445, 95% CI = 1.014–2.058, p = 0.041), compared to reversal with both FFP and PCC (27.8%, reference). Outcomes with PCC versus FFP were similar (HR = 1.075, 95% CI = 0.874–1.323, p = 0.492); 4‐factor PCC (n = 441) was associated with higher case fatality compared to 3‐factor PCC (n = 144, HR = 1.441, 95% CI = 1.041–1.995, p = 0.027). Interpretation The combination of FFP and PCC might be associated with the lowest case fatality in reversal of VKA‐ICH, and FFP may be equivalent to PCC. Randomized controlled trials with functional outcomes are needed to establish the most effective treatment. Ann Neurol 2015;78:54–62